Developing next-generation transformational leaders: Student sensemaking in leadership and change management through reflective inquiry - Suengkamolpisut, Wallapa; Singhatong, Saifon (Journal of International Students, 2026)
This study explores how students construct their understanding of transformational leadership through reflective inquiry in a leadership and change management in a global business course within an international business program in Thailand. Drawing on 120 reflective journals, the study examines how students interpreted lessons from 25 transformation leaders in Thailand and applied leadership and change theories to make sense of leadership in culturally situated contexts. Using theory-informed thematic analysis and a transformational leadership capability framework, the study traces shifts in students’ conceptions of leadership over time. The findings show movement from leader-centric and performance-focused assumptions toward more relational, ethical, and adaptive understandings of leadership, highlighting trust-building, culturally responsive communication, and inclusive change practices. The study contributes by demonstrating how reflective inquiry grounded in locally embedded leadership examples can support contextually grounded leadership learning in internationalized classrooms while promoting equity, belonging, and global engagement in global business and higher education contexts.